MENINGKATKAN LITERASI NUMERASI MELALUI PEMBELAJARAN BERDIFERENSIASI BERBANTUAN LKPD BERBASIS ETNOMATEMATIKA - Ayuningsih, Ika; Anjariyah, Deka; Wiyono, Hari Joko (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2024)
One of the important skills that students need to master is numeracy literacy. Teachers can improve this ability by integrating it into real-life context-based learning, while considering the characteristics of each student. The development of numeracy literacy can also be modified by incorporating local cultural elements. This study aims to assess the effectiveness of differentiated learning supported by ethnomathematics LKPD to improve students' numeracy literacy, reviewed from teacher activities, student activities, and numeracy literacy ability test results. The novelty of this study lies in the application of differentiated learning combined with Ethnomathematics-based LKPD that promotes Majapahit culture. The researcher used a quantitative descriptive method with a One Shot Case Study design. The sample of this study was taken using the Simple Random Sampling technique, which selected class VIII E of SMP Negeri 2 Bangsal with 32 students as the sample. Data were collected through observation and test techniques. The results of the study showed that teacher activity in managing learning was very good, student activity during the learning process was also very good, and the test results showed that 81.25% of students were included in the high numeracy literacy ability category. Thus, it can be concluded that differentiated learning with the support of ethnomathematics-based LKPD is effective in improving students' numeracy literacy skills.